Insecticidal and repellency effects of a Turkish diatomaceous earth formulation (Detech) on adults of three important pests of stored grain - Sağlam, Özgür; Bayram, Ali; Işıkber, Ali Arda; Sen, Recep; Bozkurt, Hüseyin; Hentes, Songül (Entomological Soc Turkey, Ege Univ, 2022)
In this study, laboratory experiments were conducted in order to assess the insecticidal and repellency effects of a novel Turkish diatomaceous earth (DE) formulation (Detech) on adults of the rice weevil, Sitophilus oryzae (L., 1763) (Coleoptera: Curculionidae), the confused flour beetle, Tribolium confusum du Val., 1863 (Coleoptera: Tenebrionidae), and the lesser grain borer, Rhyzopertha dominica (F., 1792) (Coleoptera: Bostrichidae). For the insecticidal activity, bioassays were conducted with soft wheat treated with 0, 600 and 900 ppm of Detech at 25 ?? 1??C and 65 ?? 5% RH and progeny production was assessed after 45 days. For the repellency tests, two-choice tests on mono-layer wheat were conducted at 1,000 ppm of Detech at 25 ?? 1??C and 65 ?? 5% RH. Overall, Detech was effective against T. confusum and S. oryzae adults in wheat, causing 82% to 100% mortality at 600 and 900 ppm after 7 and 14 days exposure. The complete, or almost complete, progeny inhibition of S. oryzae were found at both concentrations, whereas the highest reduction in R. dominica progeny (84%) was obtained at 900 ppm. Detech was highly and moderately repellent to T. confusum and S. oryzae adults, respectively, whereas it had no or low repellency effect on R. dominica adults. In conclusion, Detech, which consists of a mixture of three DE deposits with different diatom frustules has potential for use against stored-grain insect pests as a promising grain protectant. Experiments were conducted in 2020-2021 in Entomology Laboratory of Tekirda?? Nam??k Kemal University and Kahramanmara?? S??t???? ??mam University.
Keywords: Natural insecticides; repellency; Rhyzopertha dominica; Sitophilus oryzae; Tribolium confusum; wheat; Sitophilus-Oryzae Coleoptera; Tribolium-Confusum Coleoptera; Rhyzopertha-Dominica F; Inert Dusts; Efficacy; Tenebrionidae; Temperature; Wheat; Curculionidae; Populations